Exploring healthy eating among ethnic minority students using mobile technology: Feasibility and adherence. (September 2016) - Rodgers, Rachel F; Franko, Debra L; Shiyko, Mariya; Intille, Stephen; Wilson, Kelcey; O'Carroll, Dympna; Lovering, Meghan; Matsumoto, Atsushi; Iannuccilli, Alyssa; Luk, Stephanie; Shoemaker, Helen
Interventions aiming to help ethnically diverse emerging adults engage in healthy eating have had limited success. The aim of this study was to assess the feasibility of and adherence to an intervention capitalizing on mobile technology to improve healthy eating. Participants created an online photo food journal and received motivational text messages three times a day. Satisfaction with the intervention was assessed, as were control variables including depression and body dissatisfaction. In addition, weight and height were measured. Levels of adherence to the photo food journal were high with approximately two photos posted a day at baseline. However, adherence rates decreased over the course of the study. Body dissatisfaction positively predicted adherence, while body mass index negatively predicted study satisfaction. Mobile technology provides innovative avenues for healthy eating interventions. Such interventions appear acceptable and feasible for a short period; however, more work is required to evaluate their viability regarding long-term engagement.